Changes in serum markers of patients with PCOS during consecutive clomiphene stimulation cycles: a retrospective study - Marlene Hager; Steffen Hörath; Peter Frigo; Marianne Koch; Rodrig Marculescu; Johannes Ott (BMC, 2019)
Abstract Background A retrospective case-control study was performed to evaluate whether PCOS-specific serum markers would change in women with polycystic ovary syndrome (PCOS) during the course of two consecutive cycles of clomiphene citrate (CC)-stimulation, which did not lead to a pregnancy. Methods Anovulatory PCOS patients who underwent two consecutive CC-cycles (n = 41) and anovulatory PCOS controls who chose an observational approach for two months (n = 24) were included in the study. The main outcome measures were levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), anti-Mullerian hormone (AMH), total testosterone, androstenedione, and sexual hormone binding globulin (SHBG). Results In the control group, PCOS-specific serum parameters did not change during two months (p > 0.05). In the CC-group, there were decreases in LH (11.8 ± 4.9 mU/mL vs. 10.9 ± 4.0 mU/mL; p = 0.029), the LH:FSH ratio (2.1 ± 0.8 mU/mL vs. 1.8 ± 0.5 mU/mL; p = 0.007), and AMH (8.08 ± 4.27 ng/mL vs. 7.17 ± 3.37 ng/mL; p = 0.011), as well as an increase in SHBG (46.0 ± 20.2 nmol/L vs. 51.2 ± 21.0 nmol/L; p < 0.001). A higher age and lower baseline total testosterone and AMH levels were predictive of an AMH decline (p < 0.05). Conclusion Two cycles of CC-stimulation that did not lead to a pregnancy were accompanied by mean LH, AMH, and LH:FSH ratio declines and an SHBG increase. The clinical significance seems of minor relevance.